So You Want to Be a Professor? : a Handbook for Graduate Students. - Vesilind, P. . Aarne Aarne (Continuing Education Ser., 1999)
Maybe you'd like to combine the two loves of your life, teaching and scholarship, and perhaps build a satisfying and profitable academic career, but you're not sure if this is really what you want or how to go about it. Or maybe you've made up your mind but need some good advice on how to succeed. If so, this book is written for you. So You Want To Be a Professor begins with a discussion of jobs in academia and how to find them. Chapters cover a wide range of political skills for future academic success, including lecturing, organizing a course, meeting your first class, testing, maintainin.